Sociology of the COVID-19 Lockdown: Critical Analysis of Its Effects on Private School Teacher Wellbeing - Sekiwu, Denis; Ocan, Johnson (IGI Global, 2022)
Much of the research on COVID-19 is gleaned on epidemiological, virological, and medical outcomes of the global pandemic. In education, research focus is skewed towards how school closure affected the psychological disposition of learners, ignoring debate on COVID-19 effects on teachers’ social and economic wellbeing. Mandatory school closure influenced private school owners to halt teachers’ payment on the pretext that schools had no revenue. In sociological and motivational theory, such a lag in earning is certainly linked to potential decline in the teacher’s social and economic wellbeing and henceforth a huge demotivator for this group. Critical analysis of private school teachers’ social and economic wellbeing during COVID-19 and the coping mechanisms are, therefore, the subject of this chapter.
Keywords: Sociology; COVID-19 Lockdown; Private School; Teacher Wellbeing